2021
DOI: 10.3390/cells10020298
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Stress Induce PG-E2 in Murine Synovial Fibroblasts Originating from the Temporomandibular Joint

Abstract: Genetic predisposition, traumatic events, or excessive mechanical exposure provoke arthritic changes in the temporomandibular joint (TMJ). We analysed the impact of mechanical stress that might be involved in the development and progression of TMJ osteoarthritis (OA) on murine synovial fibroblasts (SFs) of temporomandibular origin. SFs were subjected to different protocols of mechanical stress, either to a high-frequency tensile strain for 4 h or to a tensile strain of varying magnitude for 48 h. The TMJ OA in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 76 publications
2
7
0
Order By: Relevance
“…With compressive strain, there was an increase in Il6 gene expression and IL6 protein secretion, while expression decreased with intermittent tension. These findings are in line with the literature [ 43 , 44 , 58 ].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…With compressive strain, there was an increase in Il6 gene expression and IL6 protein secretion, while expression decreased with intermittent tension. These findings are in line with the literature [ 43 , 44 , 58 ].…”
Section: Discussionsupporting
confidence: 94%
“…The inflammatory mediators IL6, PTGS2, and PGE 2 have already been described in connection with OA in relation to catabolic processes [ 24 , 25 , 26 , 27 , 57 ]. An increased secretion of PGE 2 was demonstrated in murine synovial fibroblasts of the temporomandibular joint and osteoblasts of the subchondral bone exposed to mechanical stress [ 44 , 57 , 58 ]. Increased expression of inflammatory factors occurs particularly during short periods of intense mechanical stress, similar to the initial stage of OA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contrary to previous results [ 43 ], RANKL gene expression was not downregulated after tensile strain in this study. In another recent study, the authors observed a trend for increased RANKL gene expression which was then associated with a reduced RANKL secretion [ 44 ]. Interestingly, the bacterial stimuli showed opposite tendencies on bone metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Keratinocytes express CXCL1, CXCL2, CXCL8, and CCL20, which recruit neutrophils and are up-regulated in psoriasis to increase inflammation [ 87 ]. CXCL1, CXCL2, and CXCL8 are mechanoresponsive proteins that are up-regulated by mechanical stimulation in keratinocytes and fibroblasts [ 88 , 89 , 90 ]. CXCR2, a G-protein-coupled receptor, is a common receptor for CXCL1, CXCL2, and CXCL8, which can promote keratinocyte proliferation and angiogenesis [ 91 , 92 ].…”
Section: Molecular Mechanismmentioning
confidence: 99%